ANALISIS DAMPAK MEDIA SOSIAL TERHADAP PERKEBANGAN PSIKOSOSIAL SISWA MI MIFTAHUL ULUM SEGARAN KEC. TIRIS KAB. PROBOLINGGO: PERSPEKTIF PENDIDIKAN ISLAM - Siti Rofiatul Adawiah; Khoiriyah (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
This study aims to examine the positive and negative impacts of social media use on the psychosocial development of elementary school (MI) students from an Islamic education perspective. In the digital era, social media has become an integral part of students' lives, influencing their social interactions, mental health, and character development. This study employed a qualitative design with a grounded research approach, allowing researchers to gather direct data from respondents' experiences and perspectives regarding the impact of social media on the psychosocial development of elementary school (MI) students in Probolinggo Regency. The results indicate that social media can have positive impacts, such as improved communication skills and access to educational information. However, social media also has negative impacts, such as online bullying, anxiety, and digital dependency. From an Islamic perspective, social media should be used wisely to strengthen moral and ethical values ​​and support good character development. Islamic education plays a crucial role in guiding students to use social media in a healthy manner, with supervision from parents and teachers, and maintaining a balance between digital and real-world life. This research makes an important contribution to the understanding of social media use in the context of Islamic education and student psychosocial development.